PERBEDAAN TEKANAN DARAH DAN NADI ORANG TERLATIH DAN TIDAK TERLATIH YANG DIBERI BEBAN 70-79% HEART RATE MAKSIMAL DENGAN MENGGUNAKAN ERGOMETER DI FAKULTAS KEDOKTERAN UNIVERSITAS ABULYATAMA - Yuni Rahmayanti; Aditya Chandra (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Background: Blood pressure is the lateral force on the artery walls by blood driven by pressure from the heart. The pulse, the blood leaving the left ventricle of the heart, is oxygen-rich and bright red in color. Methods: This research is a quasi-experimental study taken by non-probability sampling with purposive sampling method. This study was conducted to determine blood pressure and pulse before and after the exercise program in the trained and untrained groups. The research was carried out at the Physiology Laboratory of the Abulyatama Faculty of Medicine. The sample in this study amounted to 30 people, with a total sample of 15 people who were trained and 15 people who were not trained. Results: The results of the study on differences in blood pressure were obtained (P0.05) and shortness of breath was obtained (P0.05). Conclusion: The conclusion of this study is the respiratory frequency and scale of tightness in people trained borg lower than the untrained.Keywords: Blood pressure, trained pulse, untrained